Analisis Kemampuan Berpikir Kreatif Matematis dalam Menyelesaikan Soal Open Ended Persamaan Linear Satu Variabel Ditinjau Dari Kemampuan Awal Siswa (Pada Kelas VII SMP Batik Surakarta Tahun 2016/2017) - Damayanti, Herwinanda Trisnaning, Dr. Sumardi, M.Si (2017)
Math is an important subject in the world of education. One of the aims of learning mathematics is to provide students with the ability to think creatively.This study aimed to describe the creativity thinking ability on mathematics based on indicators fluency, flexibility and originality in solving open ended problem about Linear Equations One variable in terms of the ability of the early students of class VII SMP Batik Surakarta Year 2016/2017. This study is qualitative descriptive. This study in odd semester of 2016/2017 academic year. The subjects were students of VII H grade SMP Batik Surakarta. Data collection techniques using tests, interviews, and documentation. The validity of the data use a triangulation techniques and resources, namely by comparing the results of tests and interviews, as well as interviews of teachers and students. Data analysis technique include, data reduction, data presentation, and conclusion drawing. The results were obtained aspects of fluency is achieved by students proved by the students can mention the possibilities of another answer, aspects of flexibility proved by the students can use different ways of solving problems, or can at least use the correct way, as well as aspects of originality proved by students can create problems which is rarely found by other students.